Metabolic syndrome in Zambian adults with human immunodeficiency virus on antiretroviral therapy: Prevalence and associated factors. Issue 14 (9th April 2021) - Hamooya, Benson M.; Mulenga, Lloyd B.; Masenga, Sepiso K.; Fwemba, Isaac; Chirwa, Lameck; Siwingwa, Mpanji; Halwiindi, Hikabasa; Koethe, John R.; Lipworth, Loren; Heimburger, Douglas C.; Musonda, Patrick; Mutale, Wilbroad
Abstract : Abstract: Metabolic syndrome (MetS) is a constellation of factors including hypertension, abdominal obesity, dyslipidemia, and insulin resistance that separately and together significantly increase risk for cardiovascular disease (CVD) and diabetes. In sub-Saharan Africa, with a substantial burden of human immunodeficiency virus (HIV) and increasing prevalence of CVD and diabetes, there is a paucity of epidemiological data on demographic, laboratory, and clinical characteristics associated with MetS among people with HIV (people with human [PWH]). Therefore, this study aimed to determine the burden and factors influencing MetS in antiretroviral therapy (ART)-experienced individuals in Zambia. We collected cross-sectional demographic, lifestyle, anthropometric, clinical, and laboratory data in a cohort of ART-experienced (on ART for ≥6 months) adults in 24 urban HIV treatment clinics of Zambia between August, 2016 and May, 2020. MetS was defined as having ≥3 of the following characteristics: low high density lipoprotein cholesterol (HDL-c) (<1.0 mmol/L for men, <1.3 for women), elevated waist circumference (≥94 cm for men, ≥80 cm for women), elevated triglycerides (≥1.7 mmol/L), elevated fasting blood glucose (≥5.6 mmol/L), and elevated blood pressure (BP) (systolic BP ≥130 or diastolic BP ≥85 mm Hg). Virological failure (VF) was defined as HIV viral load ≥1000 copies/mL. The following statistical methods were used: Chi-square test, Wilcoxon rank-sum test, and multivariable logistic regression. Among 1108 participants, the median age (interquartile range [IQR]) was 41 years (34, 49); 666 (60.1%) were females. The prevalence of MetS was 26.3% (95% confidence interval [CI] 23.9–29.1). Age (adjusted odds ratio [OR] 1.07; 95% CI 1.04–1.11), female sex (OR 3.02; 95% CI 1.55–5.91), VF (OR 1.98; 95% CI 1.01–3.87), dolutegravir (DTG)-based regimen (OR 2.10; 95% CI 1.05–4.20), hip-circumference (OR 1.03; 95% CI 1.01–1.05), T-lymphocyte count (OR 2.23; 95% CI 1.44–3.43), high-sensitivity C-reactive protein (hsCRP) (OR 1.14; 95% CI 1.01–1.29), and fasting insulin (OR 1.02; 95% CI 1.01–1.04) were significantly associated with MetS. Metabolic syndrome was highly prevalent among HIV+ adults receiving ART in Zambia and associated with demographic, clinical, anthropometric, and inflammatory characteristics. The association between MetS and dolutegravir requires further investigation, as does elucidation of the impact of MetS on ART outcomes in sub-Saharan African PWH.